Analisis Kompetensi Lulusan melalui Kinerja Guru di SMPN Wilayah III Cirebon - Juniarti, Atty Tri; Sukartini, Titien (TRIKONOMIKA, 2014)
This study examined the phenomenon of graduates competence in SMPN Cirebon Region III. The purpose of this study is to analyze the organization school factors at SMPN Cirebon Region III, the influence of the organization school factors toward teacher competence, the influence of teacher competence toward teacher performance, and the influence of teacher performance to the graduate competence of SMPN Cirebon Region III. The types of this research are descriptive and verification, collection data used the stratified random sampling, the sample size were 266 respondents. The result of study used path analysis show there is an increased activity of primary and secondary education in the Region III Cirebon, marked by the increasing of achieved results, including APK, the average value of the UN, the average of proceed to SLA non RSBI and RSBI. Another result show that there is a closeness relationship between school organizational factors with very low and moderate relationship. Simultaneously, there is significant influence from all organizational of school factors to teachers competence’. Partially, school culture has a dominant influence than others. The last result show there is a significant influence of teachers’ competence against the teachers’ performance, and there is significant influence from the teachers’ performance against the graduates’ competence.